Analisis Keterlibatan Orang Tua Dalam Pendampingan Pembelajaran Pada Anak Usia Dini - Sari, Dianti Yunia; Lutfia, Annisa (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2019)
Abstract This research is background by lack of a study of parental involvement in learning at school. So far, there are still parents who are not very aware that actually, parents have a very important role in the child's learning process. This research was aims to describe the involvement of parents during the process in learning activities at school. There are three main subfocuses studied, (1) identify the diversity of understanding parents in learning process, (2) map the process of parental accompaniment to reflected in parentalod involvement learning activities, (3) see the impact of involvement parents based on evaluation of the process of accompaninment from parent in children learning activities. The research method employed was descriptive qualitative research with analysis with interactive analysis model. The data collection technique is done through observasion, interview, and documentation techniques. The results of the study show that: (1) parental involvement is reflected based on parenting and continuity of parenting generated through knowledge in parenting activities at school, (2) accompaniment parents in the process of learning children starting from beginning, core activities to closing shows the characteristics of parents divided into three, namely knowing through companion, not knowing but wanting to ask and not knowing not asking. (3) from the picture,it is reflected that the process evaluation of parent involvement is in the medium category, so that of periodic involvement of parent, in addition to providing psychological support to children also provides learning the information needed through experience as an accompaniment.